Adubação potássica para o cultivo de yacon - Vargas, Amanda Dutra de (2021)
The yacon (Smallanthus sonchifolius) is a plant of the Asteraceae family and comes from the Andean region, which has many nutraceutical and medicinal properties. The interest in the plant aroused due to the high content of fructooligosaccharides (FOS) presented in its roots, making yacon a functional food. Like other crops, the study of the ideal conditions for their cultivation is essential and, thus, the importance of obtaining information about the mineral nutrition of yacon is observed. As potassium is a mineral nutrient considered essential for the growth and development of all plants and one of the most accumulated nutrients in this species, the objective of the present study was to evaluate different doses of potassium fertilization in the phytotechnical and physicochemical characteristics of yacon. The experimental design used was randomized blocks (DBC), with 4 replicates per treatment, which consist of 4 different doses of potassium fertilization: 178.7 kg.ha-1; 357.4 kg.ha-1; 536.1 kg.ha-1; 714.8 kg.ha-1 of potassium chloride (KCl); and the witness: soil without fertilization. Potassium fertilization improved the chemical characteristics (higher levels of soluble solids and less acidity) and physical characteristics (less hardness, chewability, cohesiveness and adhesiveness) of yacon's tuberous roots, bringing higher quality to the final product. Since the dose of 357.4 kg.ha-1 of KCl was the one that presented the highest agronomic efficiency for the cultivation of yacon, being able to provide the greatest economic efficiency by producing larger quantities of roots in the most valued classes in the market.